2011
DOI: 10.1074/jbc.m111.241109
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Hydrophobicity or Disulfide Bridging at the Factor VIII A1 and C2 Domain Interface Enhances Procofactor Stability

Abstract: Factor VIII (FVIII) consists of a heavy (A1A2B domains) and light chain (A3C1C2 domains), whereas the contiguous A1A2 domains are separate subunits in the cofactor, FVIIIa. FVIII x-ray structures show close contacts between A1 and C2 domains. To explore the role of this region in FVIII(a) stability, we generated a variant containing a disulfide bond between A1 and C2 domains by mutating Arg-121 and Leu-2302 to Cys (R121C/L2302C) and a second variant with a bulkier hydrophobic group (A108I) to better occupy a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 26 publications
(29 reference statements)
3
29
0
Order By: Relevance
“…In addition, replacing Ala108, that localized to a hydrophobic pocket at the A1-C2 domain interface, with the more bulky Ile also showed a marked increase in FVIII stability (9). Furthermore, introducing nascent disulfide bridges between FVIII subunits by double Cys mutation at A2-A3 or A1-C2 interfaces yielded selected FVIII variants with enhanced FVIII/FVIIIa stability (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, replacing Ala108, that localized to a hydrophobic pocket at the A1-C2 domain interface, with the more bulky Ile also showed a marked increase in FVIII stability (9). Furthermore, introducing nascent disulfide bridges between FVIII subunits by double Cys mutation at A2-A3 or A1-C2 interfaces yielded selected FVIII variants with enhanced FVIII/FVIIIa stability (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that acidic residues localized to hydrophobic pockets at the A1-A2 interface (Asp519) and A2-A3 interface (Glu665 and Glu1984) when mutated to hydrophobic residues (Ala or Val), yielded favorable effects on FVIII/FVIIIa stability and /or activity (7,8). In addition, replacing Ala108, that localized to a hydrophobic pocket at the A1-C2 domain interface, with the more bulky Ile also showed a marked increase in FVIII stability (9). Furthermore, introducing nascent disulfide bridges between FVIII subunits by double Cys mutation at A2-A3 or A1-C2 interfaces yielded selected FVIII variants with enhanced FVIII/FVIIIa stability (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…FVIII Subunit Preparation-FVIIIa A1 (WT and H281S) and A3C1C2 subunit (WT) were prepared by the methods as described previously (10,11). A2 subunits (WT and S524H) were prepared using the Bac-to-Bac expression system and expressed in High Five cells (Invitrogen) as described previously (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, replacing Ala108 that localized to a hydrophobic pocket at the A1-C2 domain interface with the more bulky Ile also showed a marked increase in FVIII stability 17 . Furthermore, introducing nascent disulfide bridges between FVIII subunits by double Cys mutation at A2-A3 or A1-C2 interfaces yielded FVIII variants with enhanced FVIII/FVIIIa stability 17-19 .…”
mentioning
confidence: 96%